Design and Fabrication of Opacity Targets for the National Ignition Facility. (3rd April 2018) - Cardenas, T.; Schmidt, D. W.; Dodd, E. S.; Perry, T. S.; Capelli, D.; Quintana, T.; Oertel, J. A.; Peterson, Dominic; Giraldez, E.; Heeter, R. F.
Abstract: Accurate models for opacity of partially ionized atoms are important for modeling and understanding stellar interiors and other high-energy-density phenomena such as inertial confinement fusion. Lawrence Livermore National Laboratory is leading a multilaboratory effort to conduct experiments on the National Ignition Facility (NIF) to try to reproduce recent opacity tests at the Sandia National Laboratory Z-facility. Since 2015, the NIF effort has evolved several hohlraum designs that consist of multiple pieces joined together. The target also has three components attached to the main stalk over a long distance with high tolerances that have resulted in several design iterations. The target has made use of rapid prototyped features to attach a capsule and collimator under the hohlraum while avoiding interference with the beams. This paper discusses the evolution of the hohlraum and overall target design and the challenges involved with fabricating and assembling these targets.